PENGARUH TEKNIK RELAKSASI HAND MASSAGE TERHADAP NYERI PADA PASIEN KANKER PAYUDARA DI YAYASAN KANKER INDONESIA SURABAYA - Puput Nur Fadilah; Puji Astuti (Jurnal Ilmiah Kesehatan, 2016)
Pain is a complaint which often happens to patients diagnosed with Cancer. Patients with breast cancer will feel pain when cancerous cells enlarge, wounds occur, and if metastasis happens. One of the simple ways to decrease the pain is to use hand massage relaxation technique. Therefore, this research was purposed to find out the effect of hand massage toward pain felt by patients with breast cancer. The research applied pre-experiment one group pre-post design. The population involved the patients with breast cancer experiencing pain. 11 respondents were chosen as the samples by using the probability sampling in which simple random sampling technique was applied in this research. The data were analyzed by using paired t-test. The result of research showed that before applying hand massage, the pain level was 5.09 on average, whereas the average pain level after applying hand massage was 3.09. It showed the difference on the pain level before and after applying hand massage. Furthermore, the result of research by using paired t-test showed that p value = 0.000 and α < 0.05. The research concluded that hand massage relaxation technique brought an effect toward the pain experienced by the patients with breast cancer. Hence, the nurses in hospital should be able to do this relaxation technique to make their patients relaxed so that they can be independent in fulfilling their daily needs.